32‐1: Transparent Conductive Film at In‐Cell Touch Structure. Issue 1 (May 2016) - Shin, Sejong; Hwang, Junsik; Kim, Taeheon; Choi, Byungryul; Choi, Youngseok; Kim, Jinwuk; Shin, Sangmun; Kang, Dongwoo; Park, Kwihong; Kho, Yuseon
Abstract : Generally, ITO (Indium Tin Oxide) is almost universally used to remove ESD(Electro Static Discharge), external electric shock at the IPS Mode in LCD. However, ITO cannot be used at In‐cell touch because it has got a high conductivity. So we have developed a new material that can replace ITO and would like to introduce the research result.